2000
DOI: 10.1007/bf02820690
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Vs qualitative research methods

Abstract: Quantitative methods have been widely used because of the fact that things that can be measured or counted gain scientific credibility over the unmeasurable. But the extent of biological abnormality, severity, consequences and the impact of illness cannot be satisfactorily captured and answered by the quantitative research alone. In such situations qualitative methods take a holistic perspective preserving the complexities of human behavior by addressing the "why" and "how" questions. In this paper an attempt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…This should be based on a combination of entrepreneurial orientation and transformational leadership, and it will provide a comprehensive understanding of these two important phenomena to leaders and managers. This is because they complement each other in certain areas and phases of the research (Lakshman et al, 2000). Hence, this study has been devoted to make a model for B&H SMEs (gazelles and mice), which looks forward to being successful in terms of business performance.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%
“…This should be based on a combination of entrepreneurial orientation and transformational leadership, and it will provide a comprehensive understanding of these two important phenomena to leaders and managers. This is because they complement each other in certain areas and phases of the research (Lakshman et al, 2000). Hence, this study has been devoted to make a model for B&H SMEs (gazelles and mice), which looks forward to being successful in terms of business performance.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%
“…All data/information is in the form of numbers and analyzed by statistical techniques. This design is a descriptive correlational (Albert, 2017;Lakshman et al, 2000). This study intends to describe and find the relationship between many existing research variables, without any treatment found in experimental research.…”
Section: Methodsmentioning
confidence: 99%
“…The qualitative approach lays emphasis on meanings (Denzin & Lincoln, 2011;Willig, 2013). Thus, it is indispensable when there is a need to understand the complexities of human behavior that requires answers to "why" and "how" questions (Lakshman et al, 2000). The phenomenon of investigation in this current article is relatively new and demands linguistic data capable of providing answers to questions relating to how the girls are sexually exploited and abused following their stigmatization as witches.…”
Section: Designmentioning
confidence: 99%